SINDROM PIRAMIDAL BILATERAL MENYERUPAI KLINIS SINDROM GUILLAIN-BARRE - Putri Auliya; Ahmad Yanuar Safri; Taufik Mesiano; Winnugroho Wiratman; Fitri Octaviana; Manfaluthy Hakim (NEURONA, 2021)
A 35-year-old man came with weakness in all four limbs with ascending paralysis. The patient experienced a weakness in the right leg initially, followed by the left leg within three hours and involved both arms within one day. The patient was taken to the emergency room afterwards, and within four days, the patient developed tetraplegia, experienced weaknesses of the vocal cord and must be assisted by the ventilator. Lumbar puncture and plasmapheresis were performed, but no improvement was seen. Subsequently, the patient underwent magnetic resonance imaging (MRI) and obtained a picture of subacute infarction on bilateral medulla oblongata pyramidal seen in ????heart shape????. Patients were rehabilitated and given secondary stroke preventive therapy. Clinical findings in this patient were very similar to the clinical findings in Guillain-Barre Syndrome as this cause delayed diagnosis and therapy of the stroke. Both of these two syndromes can be life-threatening because respiratory failure can occur. Keywords: Bilateral pyramidal syndrome, GBS, Guillain-barre syndrome, stroke